Comparative Pharmacokinetics of Puerarin Alone and in Pueraria mirifica Extract in Female Cynomolgus Monkeys - Namken, Sureerat; Songvut, Phanit; Nuengchamnong, Nitra; Kemthong, Taratorn; Khemawoot, Phisit; Malaivijitnond, Suchinda (Planta Medica, 2020)
Pueraria mirifica is an endemic Thai plant that has been used for rejuvenation and in the relief of various aging diseases. Puerarin is one of the major isoflavones found in this plant and shows several pharmacological activities in relation to the Thai traditional use of P. mirifica. Therefore, comparative pharmacokinetics of pure puerarin alone and that in a P. mirifica extract in cynomolgus monkeys were conducted in order to investigate the pharmacokinetic profiles of the 2 preparations. To this end, puerarin and P. mirifica extract, at an equivalent dose of 10 mg/kg of puerarin, were orally dosed to adult female monkeys for 7 consecutive days. A single intravenous injection of puerarin at a dose of 1 mg/kg was also peformed. Serial blood samples and excreta were collected from 0 – 24 h and 0 – 48 h after dosing. Determination of the puerarin levels and its metabolites in biological samples was conducted by liquid chromatography tandem mass spectrometry. Plasma levels of aspartate aminotransferase, alanine aminotransferase, and creatinine fluctuated in the normal range, with no abnormal physical signs in the animal. The absolute oral bioavailability of puerarin was approximately 1% in both preparations. Accumulation of puerarin was found after oral dosing for 7 consecutive days in both groups. Major metabolites of puerarin found in monkeys were hydroxylation and deglycosylation products. A negligible amount of unchanged puerarin was detected in urine and feces. Pharmacokinetic profiles obtained from this study could help to design the prescribed remedy of puerarin and P. mirifica extract phytopharmaceutical products for human use.
Keywords: bioavailability; Fabaceae; Macaca fascicularis; pharmacokinetics; Pueraria mirifica; puerarin